Branched Fluorine/Adamantane Interfacial Compatibilizer for PBO Fibers/Cyanate Ester Wave‐Transparent Laminated Composites. Issue 8 (1st March 2023) - Liu, Zheng; Fan, Xiaoli; Han, Muyi; Li, Hao; Zhang, Junliang; Chen, Lixin; Zhu, Qiju; Gu, Junwei
Comprehensive Summary: Branched fluorine/adamantane PBO precursor ( pre FABPBO), synthesized via random co ‐condensation between 2, 2‐bis(3‐amino‐ 4‐hydroxyphenyl)hexafluoro propane, 1, 3‐adamantanedicarbonyl dichloride, and trimesoyl chloride, is performed as interfacial compatibilizer, bisphenol A dicyanate ester (BADCy) resin as polymer matrix, and poly( p ‐phenylene‐2, 6‐benzobisoxazole) (PBO) fibers as reinforcements to prepare PBO fibers/FABPBO‐BADCy wave‐transparent laminated composites by high temperature molding. The mechanical properties, wave‐transparent performances, and heat resistances of PBO fibers/BADCy composites are simultaneously improved by the addition of pre FABPBO. The interlaminar shear strength (ILSS) and flexural strength of PBO fibers/FABPBO‐BADCy composites are 48.9 and 665.3 MPa, respectively, increased by 33.2% and 13.3% compared to those of PBO fibers/BADCy composites (36.7 and 587.4 MPa). The dielectric constant and dielectric loss values at 10 6 Hz are 2.53 and 0.003, respectively, lower than those of PBO fibers/BADCy composites (3.06 and 0.006), and the corresponding wave transmission efficiency is 94.8%, which also presents excellent stability over the wide temperature (25—200 °C) and frequency range (10 3 —10 7 Hz and 8.2—12.4 GHz). Meanwhile, the heat resistance index and glass transition temperature are 229.9 °C and 247.5 °C, also better than those of PBO fibers/BADCy composites (229.6 °C and 247.1 °C). Abstract :